Program Results Measurement to Prove the Guidance and Counseling Program Accountability - Mufrihah, Arina; Suherman, Uman; Yustiana, Yusi Riksa (Pascasarjana UM, 2023)
Guidance and counseling program accountability faces growing demands about the extent to which the work of counselors in guidance and counseling services programs makes significant, measurable changes in students' lives, their contribution to student success and the improvement of school quality. Counselors are encouraged to work within an accountability framework together with other educators to prove that the counseling program is accountable and effective in the overall students learning process. This paper addresses the issues and challenges of results-based accountability by covering the discussion of the level of accountability level, ways of measuring key data, critical tools of accountability, analyzing critical data elements, and measurement for systemic change.